Reporting guidelines for medicinal plant extracts used in pharmacological and toxicological research: ConPhyMP - Michael Heinrich; Banaz Jalil; Mona Abdel-Tawab; Javier Echeverria; Žarko Kulić; Lyndy J. McGaw; John M. Pezzuto; Olivier Potterat; Jia-Bo Wang (University of Huddersfield Press, 2022)
Every year, the number of studies that evaluate the pharmacological effects, (clinical) efficacy or the toxicity of medicinal plant extracts is constantly increasing, but the reporting quality remains unsatisfactory. One of the main reasons is that there is a lack of detailed reporting standards for guidance. In response to this long-standing challenge, a core group of nine experts with proficiency in phytochemical analysis, including editors-in-chief of leading specialist journals, and based in different research settings globally, developed the Consensus based reporting guidelines for Phytochemical Characterisation of Medicinal Plant extracts (ConPhyMP) through a multi-staged development process. This incorporated a) a global survey among medicinal plant researchers, b) a core group, who reviewed and developed the guidelines through a Delphi process, and c) an advisory group of 20 experts, including editors of leading journals and scientific societies in medicinal plants research, who provided feedback and sanctioned the final guidelines. The ConPhyMP guidelines comprise two tables with accompanying explanatory figures. The first table provides recommendations for reporting the starting material and its initial processing, and the second table presents recommendations for conducting and reporting the analytical methods for defining the chemical profile based on the type of extracts used in the research. The group hopes that the ConPhyMP will support authors as well as peer reviewers and editors assessing these studies for publication and assist the production of evidence-based guidance of studies utilising medicinal plant extracts.